Compartmentalized Spherical Collagen Microparticles for Anisotropic Cell Culture Microenvironments. Issue 8 (21st March 2017) - Yoshida, Satoru; Takinoue, Masahiro; Onoe, Hiroaki
Abstract : This paper describes a new fabrication method for obtaining anisotropic spherical hydrogel microparticles with different types of extracellular matrix (ECM) hemispheres for use in 3D cell culture. To fabricate the microparticles, a mixture of an ECM precursor solution and sodium alginate is ejected into a calcium chloride solution under large centrifugal acceleration by a centrifuge‐based microfluidic device; the calcium alginate hydrogel plays a significant role as a "sacrificial gelation template" to maintain the ECM molecules in each hemisphere. This fabrication method enables gaining control of the hemispherical volume, density, and type of ECM. Using the microparticles, cells could be successfully encapsulated in each hemisphere selectively with high viability, which are then suitable for culture in the microparticles to form microtissues. It is believed that the proposed anisotropic ECM microparticles will facilitate the coculture of multiple cell types in different ECMs, which is similar to in vivo microenvironments, facilitating control of cell behavior in an anisotropic microenvironment for the benefit of large‐scale and quantitative analyses in vitro. Abstract : Anisotropic spherical hydrogel microparticles with different types of extracellular matrix (ECM) hemispheres for 3D cell culture. To fabricate the microparticles, a mixture of an ECM precursor solution and sodium alginate is ejected into a calcium chloride solution; the calcium alginate hydrogel plays a significant role as a type of "sacrificial gelation template" to maintain the ECM molecules in each hemisphere.